Analysis of the effect of perceived safety, brand image, mobile app quality and service quality on repurchase intention through satisfaction at Indonesia airline - Widianto, Rizwan; Ginting, Ari Maulanta (Institute of Computer Science (IOCS), 2025)
Airlines in Indonesia are competing quite competitively to achieve revenue targets, considering the decline in the number of consumers even though the Covid-19 pandemic is over. This study aims to examine the effect of perceived safety, brand image, app mobile quality and service quality on satisfaction, and its impact on repurchase intention on one of the airlines, Citilink Indonesia. This study was conducted quantitatively on 275 respondents who had flown using Citilink for at least 1x and were domiciled in Jabodetabek, Indonesia. The results of this study indicate that perceived safety, brand image, app mobile quality and service quality have a significant and positive influence on satisfaction. And satisfaction also has a significant influence on repurchase intention